Efektivitas Iklan Sebagai Pemediasi Serta Celebrity Endorser Sebagai Pemoderator Keputusan Pembelian Konsumen - Dwi Suryanto Hidayat; Lidya Rahma Norvelita (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2022)
Advertising creativity and choosing the right celebrity is believed to be able to attract the attention of the audience to make a purchase of a product. The effectiveness of advertising plays an important role as a driver of the creation of a purchase decision. This study aims to analyze the effect of advertising creativity and celebrity endorser on purchasing decisions using advertising effectiveness as a mediation, as well as to prove the role of celebrity endorsers in increasing the potential for a purchase decision to occur. The research sample used was 96 respondents, namely users of the Scarlett Whitening product. A non-probability sampling approach and limitations with purposive sampling were used in this study as the basis for data collection. Statistical tests were performed using SmartPLS. The results show that advertising creativity has a significant effect on purchasing decisions, advertising creativity also has a significant effect on purchasing decisions through mediation of advertising effectiveness. While on the other hand, this study proves the important role of celebrity endorsers in amplifying the power of advertising effectiveness in realizing consumer purchasing decisions